2007
DOI: 10.33899/rden.2007.8961
|View full text |Cite
|
Sign up to set email alerts
|

Water sorption of heat–cured acrylic resin

Abstract: Aims: To evaluate the effect of the different curing methods conventional water bath heat-curing and microwave energy curing method and different immersion periods on the water sorption and solubility of the different types of heat-cured acrylic resins. Materials and methods: Water sorption and solubility were measured by means of mass change in the materials after water saturation and dehydration. Two different commercial heat-cured acrylic resins Major Base 2, and Quayle Dental resins were used in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
1
4
0
2
Order By: Relevance
“…If residual monomer is present, less monomer conversion occurs and may result in increased sorption and solubility. (27) Tables (2and 4) and Figure (2 and 3), demonstrated that there was a significant increase in water sorption and solubility with increase times for immersion (1,4, and 12 weeks) for both curing techniques, this results is agreement with Al-Nori et al, (2007) (28) who concluded that the immersion period have an effect on the water sorption and solubility ratios of the different types of heat cured acrylic resin, also agreement with Van (2002) (29) who found that the water sorption is gradual process taking many months to complete.…”
Section: Discussionsupporting
confidence: 88%
“…If residual monomer is present, less monomer conversion occurs and may result in increased sorption and solubility. (27) Tables (2and 4) and Figure (2 and 3), demonstrated that there was a significant increase in water sorption and solubility with increase times for immersion (1,4, and 12 weeks) for both curing techniques, this results is agreement with Al-Nori et al, (2007) (28) who concluded that the immersion period have an effect on the water sorption and solubility ratios of the different types of heat cured acrylic resin, also agreement with Van (2002) (29) who found that the water sorption is gradual process taking many months to complete.…”
Section: Discussionsupporting
confidence: 88%
“…3 Resin akrilik yang direndam air selama 1 bulan mengalami ekspansi, tetapi perubahan massa yang terjadi secara klinis tidak bermakna. 4,5 Perbedaan penyimpanan berpengaruh pada gigi tiruan resin akrilik, hal ini disebabkan oleh sifat kimia dan fisik yang dimiliki resin akrilik yaitu bersifat menyerap air. Dengan perkataan lain bahwa resin akrilik dapat juga menyerap air dan udara, terutama di tempat yang lembab dengan tingkat kelembababan yang tinggi.…”
Section: Kata Kunci: Resin Akrilik Perubahan Massa Suhu Transisi Kacaunclassified
“…Beberapa penelitian menyatakan bahwa perpindahan massa berdasarkan perpindahan bahan dari satu fase ke fase lain yang berbeda dengan pemisahan yang semata-mata berdasar mekanik. 4,7,9 Terjadinya perpindahan massa karena adanya perbedaan tekanan uap atau perbedaan kelarutan. Gaya dorong yang timbul pada perpindahan massa karena adanya perbedaan konsentrasi atau gradient concentration.…”
Section: Pembahasanunclassified
“…The presented work is developed for evaluating the physical characteristics of transverse strength as well as the porosity concerning traditional longterm cured acrylic resin with the use of novel ibre lask that has been created via the ibreglass. While, the light energy created via the laser might have four interactions with target tissue (Al-Nori et al, 2007;Pick and Miserendino, 1995). {Absorption, Transmission, Re lection and Scattering}.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, vital chromophores in the intra-oral delicate tissues were Melanin, Water, Hemoglobin and in the dental hard tissues, Hydroxyapatite and Water. Various laser wave-length values have many coef icients of absorption in terms of such primary tissue components, which will make the selection of laser procedure-dependent (Al-Nori et al, 2007;Pelagalli et al, 1997;Walsh, 2003). According to the application on many tissues, using the laser application in the dentistry might be classi ied in the following way: hard tissue application and soft tissue application (Einstein, 1917).…”
Section: Introductionmentioning
confidence: 99%